РОЛЬ СОМА В АКВАЛЬНЫХ ЭКОСИСТЕМАХ ЮЖНОГО ПРИБАЛХАШЬЯ (Eurasian Journal of Ecology, 2016)
Nutrition of2995 exemplars of wels Silurus glanis from water ecosystems of the Southern part of the Balkash Lake was investigated. It was found up that here wels ate mostly food fishes like carp, bream, roach, sander, asp, grass carp, goldfish as well as noncommercial fishes like topmouth gudgeon and gray stone lach. Cannibalism was observed too. Although remains of musk-rats were found in 25 wels nutritions only, harm from wels to musk-rat Ondatra zibethicus was rather significant,. Remains of water birds were found too (in 23 fishes). Acclimatizaed here crayfish was often observed in stomaches of wels recently. People should evaluate imact of wels on water ecosystems of the Southern part of the Balkhash lake not only through concrete number of eaten animals and birds, but trough impossibilities of others to live in running waters so suitable for many animals and birds.